Efektivitas Restrukturisasi Kognitif Teknik ABC Berbasis Nilai Tasawuf dalam Menurunkan Kecemasan Karir Siswa Kelas XII - Hanina Zulfa; Hartono (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Career anxiety is a common psychological issue experienced by 12th-grade students as they prepare to continue their education or enter the workforce. Feelings of uncertainty about the future, social influences, and unrealistic beliefs often trigger anxiety that affects their career choices. The purpose of this study is to evaluate the effectiveness of ABC cognitive restructuring training rooted in Sufism in alleviating career anxiety among students. This study employed a quantitative method with a quasi-experimental design that included pretests and posttests as well as a control group. The participants consisted of 67 twelfth-grade students at SMA Negeri 3 Purwokerto, who were divided into an experimental group and a control group. The experimental group underwent an intervention in the form of ABC cognitive restructuring training based on Sufi principles, while the control group received no intervention. Data were collected using a validated and reliable career anxiety scale. Data analysis involved descriptive statistics, normality tests, independent-sample t-tests, and calculations of Cohen’s d effect size, all processed using SPSS. The findings revealed significant differences between the experimental and control groups following the intervention. ABC cognitive restructuring training inspired by Sufism is effective in minimizing career anxiety levels among college students. The application of the principle of tawakal helps students cultivate a more rational and adaptive perspective, enabling them to face future uncertainties with greater calm and a more positive attitude.